Comparisonal Analysis Of Incremental Conductance And Perturb And Observe Methods As MPPT Algorithm In Photovoltaic System - Taufik Alfajri Zulhelmi (IHSA Institute, 2021)
Photovoltaic is a semiconductor device that utilizes photon energy from the sun to be converted into electrical energy. The electrical energy produced by photovoltaic is optimized by a system called Maximum Power Point Tracking (MPPT). MPPT will find the optimal working point of the photovoltaic and keep it always working at that point. In this study, the methods used to find the optimal work point are Incremental Conductance and Perturb and Observe. MPPT is connected to the Boost Converter as a photovoltaic voltage controller. The analysis of the two MPPT methods was carried out through simulation in MATLAB/Simulink. The photovoltaic model is designed with reference to the KS80M-36 photovoltaic model. The MPPT system that has been designed is then simulated and its performance is seen. The MPPT system that has been designed using the Incremental Conductance algorithm and the Perturb and Observe algorithm has succeeded in finding the optimal photovoltaic working point and is able to respond to changes in environmental conditions by finding new optimal working points. The two MPPT systems are also able to make photovoltaic work at that optimal point. The Incremental Conductance algorithm has a power ratio of 96%, while the Perturb and Observe algorithm has a power ratio of 95.4%. The MPPT system that has been designed using the Incremental Conductance algorithm and the Perturb and Observe algorithm has succeeded in finding the optimal photovoltaic working point and is able to respond to changes in environmental conditions by finding new optimal working points. The two MPPT systems are also able to make photovoltaic work at that optimal point. The Incremental Conductance algorithm has a power ratio of 96%, while the Perturb and Observe algorithm has a power ratio of 95.4%.